The Role of Training Effectiveness and Human Resource Quality in Enhancing Employee Creativity in the Digitalization Era - Hasmin, Hasmin; Nurung, Jumiaty (Pusat Penerbitan dan Publikasi Ilmiah, FEB, Universitas Muslim Indonesia, 2024)
Proper training is one of the most critical measures businesses can implement to equip their employees with the necessary skills to confront the obstacles of globalization and digitalization. This investigation investigates the efficacy of training in fostering employee creativity by employing human resource quality as a proxy. An online survey was administered to 121 Kenshusei alums from Indonesia to collect quantitative data. Structural Equation Modeling (SEM) was implemented to ascertain the relationships between variables and the underlying causes. The findings suggest practical training improves human resources quality, fostering employee creativity. It was clear that the quality of human resources fully mediates this relationship, but training had no significant direct effect on creativity. This study uses Resource-Based Theory (RBT) and Goal-Setting Theory (GST) to argue that good training can help people become more creative and adaptable to technological changes and new needs worldwide.